Analisis Kualitas Pelayanan Pembayaran Pajak Kendaraan Bermotor di Kantor Sistem Administrasi Manunggal Satu Atap (Samsat) Kota Lima Puluh Kabupaten Batu Bara Provinsi Sumatera Utara - Ahmad Fachrizal; Isnaini Isnaini; Adam Adam (Mahesa Research Center, 2023)
The purpose of this research is to examine and analyze the quality of vehicle tax payment services and the factors that hinder the services at the Samsat Lima Puluh office in Batu Bara District, North Sumatra Province. The research method used is a qualitative approach with a descriptive design. Data collection techniques used were interviews, observations, and documentation. The research was conducted at the Samsat Lima Puluh office. The data sources used were primary and secondary data. The results of the study show that the quality of vehicle tax payment services at Samsat Lima Puluh is not yet optimal in terms of responsiveness, physical evidence, and empathy aspects. The problems related to vehicle tax payment services are due to the lack of understanding of the community (taxpayers) regarding administrative processes such as incomplete paperwork and inadequate supporting documents. Additionally, the waiting room is uncomfortable due to insufficient air conditioning, inadequate seating arrangements, and insufficient tables for filling out registration forms, resulting in taxpayers having to stand in long queues. Furthermore, the timeliness of service completion is not appropriate due to unresponsive personnel and a lack of personnel at the Samsat Lima Puluh office.